Reaktualisasi Disiplin Rohani Dalam Perspektif John Wesley Pada Era Normal Baru - Anen Mangapul Situmorang (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
The COVID-19 pandemic has changed the paradigm of many people's lives, namely the emergence of human attitudes that are aware of their limitations and begin to build a spiritually disciplined life. Humans are starting to enter a new normal era, in this era, it is easier for humans to get various information related to spiritual disciplines from various religious concepts. The thoughts of John Wesly about spiritual discipline can be a model to help the lives of Christians in carrying out spiritual discipline. This study applies a qualitative method with a phenomenological approach in the background specifically to analyze reality and conduct a literature study approach for the theoretical basis. The results of this study show that the principles of John Wesly's spiritual discipline are discipline in prayer, digging the Bible, following the sacraments, and fasting as well as showing discipline in social life. Thus, the novelty of this research is the actualization of the implementation of spiritual discipline in the context of the new normal era.